Impact of micromechanical properties of organic matter on the micro-mesopore structures of the over-mature shale in the Niutitang Formation - Hang Lei; Wenjibin Sun; Yujun Zuo; Zhonghu Wu; Qichi Dai; Wei Lv; Yueqin Li; Xionggang Xie (Scientific Reports)
Abstract The micromechanical properties of organic matter (OM) and organic pore structures in the over-mature stage are crucial for determining shale reservoir quality and assessing shale gas resource potential. However, there is still debate about the influence of micromechanical properties of OM on the micro-mesopore structures in over-mature shale. In this study, shale cores from the Niutitang Formation have been specifically chosen for OM isolation, adsorption testing, atomic force microscopy examination, and focused ion beam scanning electron microscopy (FIB-SEM) analysis to assess the micromechanical properties of OM and pore structures. The findings indicate that organic micropores and mesopores predominantly exhibit elliptical, circular, or irregular shapes. Organic pores mainly provide pore volume (PV) and specific surface area (SSA) of shale. In the over-mature stage, residual kerogen and pyrobitumen transition towards a graphite structure, increasing Young’s modulus of OM. Additionally, as thermal maturity increases, the absence of a rigid mineral framework and pore fluid pressure results in the compaction of pores, leading to a decrease in PV and SSA. The organic micropores are more vulnerable to collapse and compaction because of the increased brittleness of OM. The organic micropores and mesopores gradually evolve from regular circular and elliptical shapes to irregular shapes during the over-mature stage. The research findings provide valuable insights into the micromechanical mechanism of pore evolution in over-mature marine shale within complex structural regions.